2019
DOI: 10.11646/zootaxa.4609.2.3
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Amolops (Anura: Ranidae) from China, with taxonomic comments on A. liangshanensis and Chinese populations of A. marmoratus

Abstract: Amolops shuichengicus sp. nov., a new species of the A. mantzorum group is described from Guizhou, southwest China, on the basis of significant molecular divergences in 16S + CO1 genes and the combination of morphological characteristics: small body size, SVL 34.6–39.6 mm in adult males and 48.5–55.5 mm in adult females; dorsal skin relatively smooth; presence of vomerine teeth; presence of cream maxillary gland from lower edge of eye to the anterior of supratympanic fold; presence of supratympanic folds and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 773 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…Bayesian analyses were conducted using MrBayes 3.2.7 with the Marko chain Monte Carlo (MCMC) for 20,000,000 generations and 1000 sampled generations (Ronquist et al 2012). The phylogenetic tree indicated that the mitogenome of A. jinjiangensis and A. loloensis clustered together, which supported the phylogenetic inferences estimated by Lyu et al (2019) and Zeng et al (2020) with samples also from Deqin County in Yunnan Province, but conflicted with those from Zhongdian County in Yunnan Province (Lu et al 2014). Furthermore, our analyses recovered a sister taxa relationship between A. jinjiangensis þ A. loloensis and A. mantzorum þ A. tuberodepressus.…”
Section: Disclosure Statementsupporting
confidence: 76%
See 2 more Smart Citations
“…Bayesian analyses were conducted using MrBayes 3.2.7 with the Marko chain Monte Carlo (MCMC) for 20,000,000 generations and 1000 sampled generations (Ronquist et al 2012). The phylogenetic tree indicated that the mitogenome of A. jinjiangensis and A. loloensis clustered together, which supported the phylogenetic inferences estimated by Lyu et al (2019) and Zeng et al (2020) with samples also from Deqin County in Yunnan Province, but conflicted with those from Zhongdian County in Yunnan Province (Lu et al 2014). Furthermore, our analyses recovered a sister taxa relationship between A. jinjiangensis þ A. loloensis and A. mantzorum þ A. tuberodepressus.…”
Section: Disclosure Statementsupporting
confidence: 76%
“…The phylogenetic tree indicated that the mitogenome of A. jinjiangensis and A. loloensis clustered together, which supported the phylogenetic inferences estimated by Lyu et al. ( 2019 ) and Zeng et al. ( 2020 ) with samples also from Deqin County in Yunnan Province, but conflicted with those from Zhongdian County in Yunnan Province (Lu et al.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Guizhou Province, China is an important part of southwestern China, especially concerning the particular environments of karst rocky desertification, and knowledge of biodiversity levels and/or patterns are still seriously lacking in this region. Recently, a series of new amphibian species were described from Guizhou Province (Zhang et al 2017;Li et al 2018aLi et al , b, 2019aLyu et al 2019;Wang et al 2019c;Luo et al 2020;Liu et al 2020;Wei et al, 2020;Xu et al, 2020, highlighting the underestimation of the species diversity of this province. For the genus Megophrys, molecular phylogenetic differences still suggested some cryptic species in or near this region (Liu et al 2018), but Megophrys anlongensis sp.…”
Section: Discussionmentioning
confidence: 99%
“…M. feae Boulenger, 1887 Boulenger 1887 M. feii Yang et al 2018 M. flavipunctata Mahony, Kamei, Teeling & Biju, 2018Mahony et al 2018 (Ohler, 2003) Ohler 2003 M. gigantica Liu, Hu & Yang, 1960Liu et al 1960 M. glandulosa Fei, Ye & Huang, 1990Fei et al 1990 (Ohler, 2003) Ohler 2003 M. himalayana Mahony, Kamei, Teeling & Biju, 2018Mahony et al 2018 M. hoanglienensis Tapley, Cutajar, Mahony, Nguyen, Dau, Luong, Le, Nguyen, Nguyen, Portway, Luong & Rowley, 2018Tapley et al 2018 M. huangshanensis Fei & Ye, 2005 Fei and Ye 2005 M. insularis (Wang, Liu, Lyu, Zeng & Wang, 2017) Wang et al 2017a M. intermedia Smith, 1921Smith 1921 M. jiangi Liu, Li, Wei, Xu, Cheng, Wang & Wu, 2020 Liu et al 2020 M. jingdongensis Fei & Ye, 1983Fei et al 1983 (Wang, 2012) Wang et al 2012 M. jiulianensis Wang, Zeng, Lyu & Wang, 2019 Wang et al 2019b M. kalimantanensis Munir, Hamidy, Matsui, Iskandar, Sidik & Shimada, 2019Munir et al 2019 M. kobayashii Malkmus & Matsui, 1997Malkmus and Matsui 1997 M. koui Mahony, Foley, Biju & Teeling, 2017Mahony et al 2017 M. kuatunensis Pope, 1929Pope 1929 M. lancip Munir, Hamidy, Farajallah & Smith, 2018Munir et al 2018 M. leishanensis Li, Xu, Liu, Jiang, Wei & Wang, 2018 Li et al 2018 M. lekaguli Stuart, Chuaynkern, Chan-ard & Inger, 2006Stuart et al 2006 (Zhang, Li, Xiao, Li, Pan, Wang, Zhang & Zhou, 2017) Zhang et al 2017 M. ligayae Taylor, 1920 Taylor 1920…”
mentioning
confidence: 99%